The use of nanoferromagnetics to increase the cytotoxic effect of antitumor drugs - Chekhun, V.F.; Todor, I.N.; Lukyanova, N.Yu.; Shpyleva, S.I.; Naleskina, L.A.; Khaetsky, I.K.; Kulik, G.I. (Experimental Oncology, 2009)
Aim: To investigate the influence of ferromagnetic nanoparticles on antitumor effect of doxorubicin and mitochondria oxidative phosphorylation. Methods: The study was carried out on the mice-hybrids (C57Bl/6xDBA/2) with intraperitoneally (i/p) transplantated Ehrlich ascitic carcinoma. Single i/p injection of doxorubicin (Dox), stabilized ferromagnetic nanoparticles (Fe3O4; 20–40 nm; FM) or their combination were performed 7 days after tumor transplantation. The cytotoxic effect of agents, morphology and cell cycle of tumor cells were studied 24, 48 and 72 h after Dox administration. Results: The investigations showed that ferromagnetic nanoparticles increased the cytotoxic effect of doxorubicin on Ehrlich ascіtic carcinoma mainly 48 h after agents’ administration. The largest number of apoptotic cells was observed in group of animals in which doxorubicin was administered before ferromagnetic nanoparticles. Moreover, the ferromagnetic nanoparticles at concentration 1.45 μg Fe/ml and, particularly, 7.25 μg Fe/ml decreased mitochondria oxygen consumption in phosphorylation state that may negatively influence their living capability. Conclusions: Obtained data point out the perspective of use of certain sized FM nanoparticles to increase the cytotoixc effect of antitumor drugs.